Brain-gut miscommunication : biopsychosocial predictors of quality of life in irritable bowel syndrome - Pletikosić, Sanda (Array, 2018)
Irritable bowel syndrome (IBS) is a complex disorder that results from interactions of numerous factors. The biopsychosocial model describes a number of predisposing, precipitating, and perpetuating factors, which contribute to the onset and maintenance of symptoms and consequently to quality of life (QoL) impairment. The aim of this study was to examine the impact of several psychological and biological factors on the physical and mental components of QoL in IBS patients. A total of 46 IBS patients completed a set of questionnaires (Big Five Inventory, State-Trait Anxiety Inventory, Beck Depression Inventory-II, Medical Outcome Study Short-Form 36) and kept a diary of their mood, daily stress, and symptoms over a period of two weeks. Patients' heart rate variability, serum cortisol, and fecal calprotectin levels were also measured. The results of regression analyses showed that depression (β = -.30) and negative mood (β = -.28) predicted physical QoL, while depression (β = -.45) and positive mood (β = .33) significantly predicted mental QoL. The model, which included calprotectin, cortisol, anxiety, depression, and positive and negative mood, explained a total of 47% of variance of physical and 57% of variance of mental QoL. Our results confirm the role of negative affect in IBS QoL impairment. They also indicate that biological factors seem important for physical QoL in IBS patients. The role of positive mood as a protective factor for mental QoL might be significant for psychological interventions with IBS patients.